AWARENESS INFLUENCE TAXPAYER, TAX AUTHORITIES AND KNOWLEDGE QUALITY SERVICE TAXPAYERS TAX INCOME TAX AVOIDANCE MEASURES AGAINST SMES (A Case Study Market Environment Pujasera Subang) - Sukarno Hadi Wibowo (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2019)
This study aims to find evidence of research on the factors that influence on the tax evasion measures. Factors tested in this research that the taxpayer awareness, quality of service and knowledge of the taxpayer tax authorities abouttaxes. Data obtained using simple random sampling method, the sample is used as much as 79 respondents. Data were analyzed using multiple linear regression in SPSS softwareversion 17.0. Results from this study indicate that the variable taxpayer awareness, quality of service tax authorities and tax payers knowledge of tax simultaneously significantly influence the actions of tax evasion, it is seen from the results of testing the hypothesis that gained significance level of 0.000 less than 0.05, andseen from the calculated F value of 47.689 which is greater than the F table at 2.73. The partial variable taxpayer awareness, quality of service tax authorities and tax payers knowledge of tax significant effect on income tax evasion action SMEs.